The Kisa Noun Phrase - Ondondo, Emily A. (David publishing, 2015)
The phrase is a significant unit of analysis in the grammar of any language. It is not only studied at the syntactic level but also at other levels of analysis-phonology, morphology, semantics, and pragmatics. Different types of phrases have been identified and described in the grammar of English and other languages. However, the noun and verb phrases are the most important and widely described phrases given that the structure of many languages revolves around the noun and the verb word. Though, there are some studies on the noun phrase in Bantu languages. There is no study whatsoever in the literature dealing with the noun phrase in Kisa, a Bantu language spoken in Western Kenya. Moreover, the studies on the noun phrase in Bantu have looked only at the constituents of the noun phrase and their permissible order without considering the relationships that hold between or among these constituents. Adopting a descriptive design and using data generated by the author as a native speaker of Kisa, this paper identifies and describes the syntactic structures that constitute noun phrases in Kisa. It delineates the elements that form a noun phrase and explains how they combine. The paper then explains the relationships that hold between these elements by providing syntactic and morphological evidence. The paper shows that a noun phrase in Kisa has an obligatory element which is the head of the phrase and optional elements. There are those optional elements that need the head to make sense. These are closely linked to and in a dependency relationship with the head. Those optional elements that do not need the head to make sense are loosely linked to it and are not in a dependency relationship with the head.
Keywords: noun, phrase; head; dependents; dependency; apposition